To what extent does business relationship (Guanxi) contribute to Business success, especially retail business success in China? - Zhang, Chen (2010)
Abstract This dissertation examines the importance of relationship regarding to the business operation in Chinese market. The term of Guanxi is emphasized according to the specific business features, especially the retail business’ characters in China. The aspects of customer, suppliers and government relationships were defined in terms of detailed research directions. A fieldwork was carried out in a selected organization—Hualian, and the research methods of questionnaire and interview were implemented for data collection. As demonstrated form the research study, regarding to the areas of customer, suppliers and government, Guanxi is proved to be an important factor in terms of firms’ assets of competing in the Chinese market. Thus, as to the current situation of Chinese business environment, to build up good relationship with internal and external parties is critical to companies’ success.